Single ring isolation for atrial fibrillation ablation: Impact of the learning curve. (2nd February 2022) - Thiyagarajah, Anand; Mahajan, Rajiv; Iwai, Shinsuke; Gupta, Aashray; Linz, Dominik; Chim, Ivana; Emami, Mehrdad; Kadhim, Kadhim; O'Shea, Catherine; Middeldorp, Melissa E.; Lau, Dennis H.; Sanders, Prashanthan
Abstract: Introduction: Although single ring isolation is an accepted strategy for undertaking pulmonary vein (PV) and posterior wall isolation (PWI) during atrial fibrillation (AF) ablation, the learning curve associated with this technique as well as procedural and clinical success rates have not been widely reported. Methods and Results: Prospectively collected data from 250 consecutive patients undergoing de novo AF ablation using single ring isolation. PWI was achieved in 212 patients (84.8%) and PV isolation without PWI was achieved in 37 patients (14.4%). Thirty‐one cases (12.4%) demonstrated inferior line sparing where PWI was achieved without a continuous posterior wall inferior line. A learning curve was observed, with higher rates of PWI (98% last 50 vs. 82% first 50 cases, p  = .016), higher rates of inferior line sparing (20% last 50 vs. 8% first 50 cases, p  = .071) and lower ablation times (43.8 min (interquartile range [IQR]: 34.6–57.0 min) last 50 versus. 96.5 min (IQR: 80.8–115.8 min) first 50 cases; p  < .001). Three (1.3%) major procedure‐related complications were observed. Twelve‐month, single‐procedure freedom from atrial arrhythmia without drugs was 70.5% (95% confidence interval [CI]: 61.5%–77.7%) and 60.0% (95% CI: 50.2%–68.4%) for paroxysmal and persistent/longstanding persistent AF. Twelve‐month multi‐procedure freedom from atrial arrhythmia was 92.2% (95%CI: 85.6%–95.9%) and 85.6% (95%CI: 77.2%–91.0%) for paroxysmal and persistent/longstanding persistent AF. Conclusion: Employing a single ring isolation approach, PWI can be achieved in most cases. There is a substantial learning curve with higher rates of PWI, reduced ablation times, and higher rates of inferior line sparing as procedural experience grows. Long‐term freedom from arrhythmia is comparable to other AF ablation techniques.